"n Preek vol aanhalings: Miga 1 vanuit "n redaksie-historiese perspektief - Strydom, J. G. (Hervormde teologiese studies, 1989)
A sermon full of quotations: Micah 1 from a redactionhistorical perspective In his Micah commentary, published in 1976, AS van der Woude holds the view that Micah 1 has to be understood as a literary and historically-original unit, a sermon which Micah delivered at Lachish. In this article it is agreed that Micah 1, in its present form, indeed forms a literaty unit (a sermon), but against Van der Woude, the thesis is put forward that the sermon does not form a historically-original unit; it rather underwent a historical development in the sense that Micah, in delivering the sermon in 701 BC (not 722/1 BC as Van der Woude suggests), made use of (quotations from) two prophecies, spoken by himself, against Samaria (722/1 BC) and Jerusalem (714-711 BC). The present form of the chapter therefore has to be ascribed to Micah himself, and not to the redactor of the book.